Assessing the acceptability and feasibility of financial incentives to increase cervical cancer screening among women in vulnerable situations in Italy: a formative research protocol - Cristina Lumia; Francesca Squillace; Francesca De Nard; Francesca Marchetti; Davide Ausili; Simona Fumagalli; Antonella Nespoli; Alexandre Dumont (Archives of Public Health, 2026)
Abstract Background Cervical cancer screening is a cornerstone of cancer prevention; however, participation remains socially patterned even within universal healthcare systems. Financial or economic incentives have been proposed to improve screening participation among vulnerable women, yet evidence regarding their acceptability, ethical implications, and implementation feasibility within European universal healthcare contexts remains limited. This study aims to inform the design of an equity-oriented incentive-based cervical cancer screening strategy for women in vulnerable situations in Italy. Methods The study integrates three components: (1) a policy and document review examining regulatory, organisational, and ethical conditions for implementation; (2) a system readiness assessment across Non-Governmental Organizations, the local Health Protection Agency (ATS), and community screening services (CSS- Consultori Familiari ); and (3) empirical mixed-methods research including a cross-sectional survey ( n ≈ 150–200), in-depth interviews with eligible participants, and 3–4 focus group discussions with professionals and stakeholders. Quantitative and qualitative data will be analysed separately and integrated using a convergent mixed-methods approach to identify behavioural and implementation determinants and refine the Theory of Change. Discussion This formative implementation study will generate context-specific evidence on behavioural, organisational, and system determinants influencing the acceptability and feasibility of incentive-based cervical cancer screening strategies within a coordinated NGO-ATS-community services pathway. Findings will inform the co-design of an ethically acceptable and system-compatible implementation strategy to support equitable screening participation among women in vulnerable situations and guide subsequent pilot testing and evaluation. Trial registration Open Science Framework (OSF), registration ID: osf.io/d45xt, registered 28 December 2025.